A bond-line porosity model that integrates fillet shape and prepreg facesheet consolidation during equilibrated co-cure of sandwich composite structures. (December 2020) - Niknafs Kermani, Navid; Simacek, Pavel; Advani, Suresh G.
Abstract: Honeycomb core sandwich structures are co-cured to bond partially cured thermoset prepreg facesheets with an adhesive layer to both sides of the honeycomb core under a pre-defined pressure and temperature cycle in an autoclave. In the Equilibrated (Open-core) co-cure process, the honeycomb core cells are vented to the vacuum bag. Although the co-curing is advantageous over the secondary bonding process of sandwich structures, it is strongly dependent on the materials and process parameters and could result in high porosity within the bond-line. In this paper, we present a comprehensive model for the evolution of the bond-line porosity in which we introduce and couple new models for the bond-line fillet shape and the void escape process from the bond-line with the facesheet consolidation and the porosity models. First, a model is proposed to simulate the adhesive bond-line fillet shape. Next, a previously formulated prepreg facesheet consolidation model is used to calculate the amount of prepreg resin containing voids that bleed into the bond-line. A diffusion model of bubble growth tracks the porosity within the bond-line as a function of the cure cycle. The fillet shape allows one to estimate the number of bubbles that escape from the bond-line. The cure kinetics and the gelation time of the prepreg resin and the adhesive dictate the entrapment of the voids and the porosity evolution within the bond-line. The usefulness of the integrated model is demonstrated with an example in which it is shown that if an adhesive with perforations is used or if the gelation of the adhesive triggers after the gelation of the resin it will result in lower porosity. The results of this example are validated with a reported experimental study with the same material properties and processing conditions.